Design of an Interactive Multimedia Gallery Based on Experiential Architecture and Environmental Analysis in Surabaya - Dhimas Aulia Rahmawan; Ibrahim Tohar; Suko Istijanto (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Rapid digital transformation in urban environments has changed the way people access information and experience cultural spaces, increasing the demand for interactive and immersive architectural environments. In Surabaya, the availability of multimedia-based cultural facilities that integrate spatial experience and digital interaction remains limited. This study aims to develop a design framework for an Interactive Multimedia Gallery using an Experiential Architecture approach that integrates environmental responsiveness and multisensory spatial experience. The research focuses on a site located on Mayjend Sungkono Street, Surabaya. A qualitative-descriptive method combined with a design-based research approach is applied, including field observation, literature review, and environmental analysis. The findings indicate that environmental factors such as solar orientation, wind patterns, noise levels, and urban context significantly influence spatial zoning and design strategies. These conditions determine the arrangement of public, transitional, and immersive spaces within the gallery. Furthermore, experiential design strategies such as spatial sequencing, lighting modulation, material articulation, and interactive multimedia integration contribute to creating an immersive user experience. The study concludes that integrating environmental analysis with experiential architecture is essential for producing adaptive, interactive, and context-responsive cultural spaces in urban environments.